Left Atrial Appendage Closure Devices For Stroke Prevention - Kapur, Sunil (Arrhythm Electrophysiol Rev, 2014)
Cardioembolic stroke is a major cause of morbidity and mortality in patients with atrial fibrillation (AF). The left atrial appendage (LAA) is the prominent source of clot formation. While systemic anticoagulation is the current standard of care, anticoagulants carry many contraindications and possible complications. Techniques for elimination of the LAA are in various stages of development and early clinical use. In the coming years, accumulating data will help guide the management of AF patients at risk of bleeding as well as potentially become first-line therapy to reduce the risk of thromboembolic stroke. The purpose of this article is to review current endovascular and epicardial catheter-based LAA occlusion devices and the clinical data supporting their use.